Blueberry and blackberry are tolerant to repeated indaziflam applications. (19th August 2021) - Grey, Timothy L.; Hurdle, Nicholas L.; Rucker, Keith; Basinger, Nicholas T.
Abstract: Numerous perennial horticultural crops are grown across the southeastern United States. Blueberry and blackberry (also known as caneberry) are commonly found in roadside stands, promote agritourism via pick-your-own markets, are important for fresh market commercial production in the region, and when processed, provide desirable value added products. Season-long weed control using residual herbicides is crucial for these perennial fruit crops to maximize berry quality and yield. Studies performed from 2012 to 2014 in Lanier and Clinch counties in Georgia evaluated the effects of repeated applications of indaziflam at 35, 75, or 145 g ai ha −1 applied biannually in March and September (five total applications) on growth of 'Alapaha' rabbiteye and 'Palmetto' highbush blueberry, and 'Apache' thornless blackberry. All indaziflam treatments were mixed with glufosinate, and a glufosinate-only treatment was included as a check. Minor leaf chlorosis (<10%) was noted within 30 d after application for all blueberries for all treatments, but this was always transient. Blueberry stem diameter was not different for any treatment, even when indaziflam was applied up to 725 g ai ha −1 over 3 yr as compared to glufosinate alone. There was no chlorosis or stem diameter differences for blackberry noted for any treatment. Indaziflam applied in blueberry and blackberry production provides season-long control of numerous troublesome weed species, without causing injury or negatively impacting crop growth.